2010
DOI: 10.1194/jlr.m008359
|View full text |Cite
|
Sign up to set email alerts
|

FADS genetic variants and ω-6 polyunsaturated fatty acid metabolism in a homogeneous island population

Abstract: This article is available online at http://www.jlr.org Supplementary key words fatty acid desaturase • isolated population • genetic association Several changes in diet over the past century are hypothesized to have been maladaptive, thereby leading to an increase in the incidence of numerous chronic diseases in developed countries ( 1, 2 ). Many of these diseases (obesity, diabetes, asthma, allergies, arthritis and chronic joint disease, dementia, and cardiovascular disease) have a substantial infl ammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 43 publications
8
56
1
1
Order By: Relevance
“…We hypothesize that prostanoid production in vivo is directly and importantly influenced by the effective concentration and FA composition of the milieu in which PGHSs operate, what we term the FA tone. We presume that every individual establishes a fairly constant FA tone as a consequence of dietary habits and genetic profile (45,46). We imagine that having a FA tone outside some normal range would change prostanoid formation to an extent sufficient to affect the health of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that prostanoid production in vivo is directly and importantly influenced by the effective concentration and FA composition of the milieu in which PGHSs operate, what we term the FA tone. We presume that every individual establishes a fairly constant FA tone as a consequence of dietary habits and genetic profile (45,46). We imagine that having a FA tone outside some normal range would change prostanoid formation to an extent sufficient to affect the health of an individual.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data suggest that the n-6 PUFAs in breast milk, plasma and blood cell membranes across all ages are more affected by FADS polymorphisms than n-3 PUFAs, typically with an increase in LA and a decrease in AA-levels in minor allele carriers (55,56,(60)(61)(62)(63). However, we have recently found that FADS polymorphisms contributed substantially to DHAstatus in late infancy, and some SNP minor alleles were even found to up-regulate DHA-status (60), whereas minor alleles of all the investigated SNPs lowered AA in a consistent way (64).…”
Section: Role Of Genetic Variability In Lcpufa Levels and Functional mentioning
confidence: 94%
“…Briefly, 100 mg tissue was added to a glass tube containing 2 ml of 4:1 methanol and hexane and 100 µg butylated hydroxytoluene. After homogenization on ice and flushing a tube with nitrogen for 20 s, 200 µl of acetyl NCBI dbSNP database) in the FADS gene cluster, where two desaturase genes, FADS1 and FADS2, for the ARA and DHA synthesis are located, were generally associated with a lower product/substrate ratio of n-6 and n-3 PUFAs in serum or red blood cells (RBCs), indicating lower capacity of ARA, DHA synthesis (18)(19)(20)(21)(22). Furthermore, the allele frequency of the FADS cluster differs among populations; some minor alleles in most populations occur predominantly in certain populations (23,24), suggesting environmental effects on the allele frequency.…”
Section: Total Lipid Extraction Thin-layer Chromatography and Methymentioning
confidence: 99%